Analisa komparatif percepatan tanah maksimum akibat gempabumi M6.3 di Selat Mentawai berdasarkan rumusan empiris Ground Motion Prediction Equation (GMPE) (Comparative analysis of the maximum ground acceleration due to the M6.3 earthquake in the Mentawai Strait based on the empirical formula of Ground Motion Prediction Equation (GMPE) ) - Fitri Anggriani; - Akmam; - Syafriani (PILLAR OF PHYSICS, 2018)
The ground motion intensity caused by an M 6.3 earthquake that struck Mentawai Strait on September 1st, 2017 with epicenter -1.24 N and 99.75 E and depth 58 km were recorded on BMKG’s seismic and intensity network, the intensity was about III - IV intensity scale (MMI) and the acceleration was 2.8 g. The earthquake intensity calculation in Indonesia can also be calculate by using Ground Motion Prediction Equation (GMPE) such as Si and Midorikawa (1999), Mc Guire (1963), Donovan (1973) and Wu et al (2003) empirical equations. We conducted a research to compare the peak ground acceleration calculation between using empirical equation and by using data observed on BMKG’s intensity networks. The PGA  result on every district of Sumatera Barat Province that shown on BMKG’s shakemap has a significant different comparing with the calculation using the equations. The PGA values by using the empirial equations were decayed through the hipocenter distance of the earthquake in every district of Sumatera Barat Province. Meanwhile base on the observed one, we found some anomalies of PGA value on some BMKG’s accelerograph station networks i.e. PDSI in Padang and PAPA in Padang Panjang with 14.35 g and 5.07 g respectively. But these anomalies were not impacted to the result of the intensity, because they have some filters that can elimunate these kind of anomalies to conduct an accurate result.